Graph Mining for Traffic Source Similarity Search - Ekmanis, M. (Elektronika ir Elektrotechnika, 2010)
This work represents a method of describing individual host role in the network, based on their relationships with other hosts. The method relays only on a fact that there is communication between pair of hosts, without taking into account unreliable information about payload, port numbers, protocols, etc. Single and multi sensor traffic flow captures aspects are analyzed. The gain of the concept implementation shows the ability of algorithm to group similar traffic sources together.